(3ecGaMI GdYed GdLHQi h GdGJLGQ HGdHTQ ai GdbGfhf GdeUQi GdebGQf (B/ s - (3QGfjG YHOGdefYe YHOGdMejOs; (3CMeO MSf GdHQYis; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2019)
(3jJdNU ehVhY gPg GdQSGdI ai OQGSI GdYed GdLHQj h GdGJLGQ HGdHTQ ai GdbGfhf GdeUQi GdebGQf(B: (3MjK JWQbfG ef NdGd gPg GdQSGdI Gdi eaghe GdGJLGQ HGdHTQ h GdYed GdLHQi ai GdGJaGbjdJ GdOhdjI; h GdJYQjaGJ GdeJTGHgI h GdeJWGHbI eY GdYed GdLHQi h ehba GdJTQjYGJ GdebGQfI ef GdGJLGQ HGdHTQ(B. (3ceG QcRfG Ydi GdGSHGH GdeDOjI dgPg GdXGgQI h efgG GdGSHGH GdeHGTQI Gh GdGSHGH GdZjQ eHGTQI(B: (3h HMKfG JbOjQGJ GdYed GdLHQi GdUGOQI ef efXeI GdYed GdOhdjI ef YGe (B2005 (3Gdi YGe (B2016 . (3h ai GdHGH GdKGfi ef gPg GdQSGdI GSJYQVfG GfhGY GdYed GdLHQi h GdGJLGQ HGdHTQ MjK JWQbfG ddGfhGY h GdGTcGd GdJbdjOjI h GdMOjKI ddGJLGQ HGdHTQ(B: (3h HMKfG CjkVG ai GdHGH GdKGdK OhQ eUQ GdbGfhfi ai ecGaMI GdYed GdLHQi h ddGJLGQ HGdHTQ(B. (3h bOefG aj NGJeI GdOQGSI eLehYI ef GdebJQMGJ GdJi jecf GdGaGOI efgG ai GdGSgGe ai GdMO ef XGgQI GdGJLGQ HGdHTQs
(3jTJed Ydi edGMb(B: (3UaMGJ (B383-390s
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdJTQjYGJ GdELJeGYjI, (B2019s
(3HHdjhLQGajG(B: (3UaMGJ (B391-427s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdJTQjYGJ GdELJeGYjIs; (3GdGJLGQ HGdHTQs; (3GdYed GdLHQis; (3GdbGfhf GdeUQis; (3eGgjI GdYed GdLHQj hGdGJLGQ HGdHTQs; (3CSHGH hYhGed XGgQI GdYed GdLHQjs; (3JYQja hJbSjeGJ GdYed GdLHQjs; (3CfhGY GdYed GdLHQj ef CTcGd JbdjOjI hMOjKIs; (3OhQ GdbGfhf GdeUQj aj ecGaMI GdGJLGQ HGdHTQ hGdYed GdLHQjs; (3bGfhf JfXje RQY GdCYVGA GdHTQjIs; (3bGfhf GdgLQI ZjQ GdTQYjIs; (3GdhVY GdbGfhfj dYeGd GdNOeI GdefRdjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdJTQjYGJ GdELJeGYjIs